MENGEMBANGKAN KEMAMPUAN ANAK BERCERITA DENGAN METODE PEMBERIAN TUGAS MENGGAMBAR - Ahmad Fachrurrazi; Sitti Kibtiyah (JOEL: Journal of Educational and Language Research, 2022)
This research is motivated by the importance of the development of story-telling ability in early childhood. One of stimulation in the development is the story, as the skills to make a variety of images. With the formulation of the problem is "Do the methods of drawing tasks affect the ability to tell the students in group B TK Wijaya Bendul Mrisi Surabaya?. The purpose of this study was to determine the effect of the method of administration tasks such as drawing on the ability to tell the students in group B TK sill Merisi Wijaya Surabaya. The study was designed according to the concept of Pre-experimental One group Pre and Post test design. Data collected by the method of performance tests with instrument observation sheet performance. The experiment was conducted on students in kindergarten kolompok sill Merisi Wijaya Surabaya by the number of learners 35 children. Based on the analysis of data obtained using a T-test t calculate equal to 6.883 while t table of 2.032 with 35 degrees of freedom and a confidence level of 0.5 means Hi accepted. From the results of this study concluded that the method of administration tasks such as drawing an effect on children's storytelling ability.